Nursing role during COVID-19 vaccination - Arévalo-Ipanaqué, Janet Mercedes (2021)
Since the emergence of COVID-19 in December 2019 and its declaration as a pandemic in the following months, this disease has been causing anxiety in the world population for more than a year due to its high transmissibility accompanied by the absence of effective treatment. The capacity of the virus is such that its basic reproduction, an indicator of virus transmissibility, has been estimated with an average value of 3.28 and a median of 2.79, so it is assumed that, in an environment without containment measures, an infected person could infect more than two people in a period of three to four days.